2007
DOI: 10.1016/j.molimm.2006.11.020
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for preferential Ig gene usage and differential TdT and exonuclease activities in human naïve and memory B cells

Abstract: Memory B cells and the antibodies they encode are important for protective immunity against infectious pathogens. Characterization of naïve and memory B cell antibody repertoires will elucidate the molecular basis for the generation of antibody diversity in human B cells and the optimization of antibody structures that bind microbial antigens. In this study we aimed to investigate the influence of antigenic selection on the antibody genes of the two CD27 + memory B cell subsets, comparing them with the naïve r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
38
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 41 publications
(45 citation statements)
references
References 43 publications
7
38
0
Order By: Relevance
“…Consistent with previous studies of randomly selected naive or memory B cells, analysis of H chain CDR3 regions suggested significantly shorter CDR3 lengths in RV-specific IgD ϩ CD27 ϩ memory B cells than in naive cells (24,25). As shown in Fig.…”
Section: Rv-specific Cd19 ϩ Igd ϩ Cd27 ϩ Memory B Cells Harbor Shortesupporting
confidence: 91%
“…Consistent with previous studies of randomly selected naive or memory B cells, analysis of H chain CDR3 regions suggested significantly shorter CDR3 lengths in RV-specific IgD ϩ CD27 ϩ memory B cells than in naive cells (24,25). As shown in Fig.…”
Section: Rv-specific Cd19 ϩ Igd ϩ Cd27 ϩ Memory B Cells Harbor Shortesupporting
confidence: 91%
“…These data support emerging evidence that the IgM memory repertoire is genetically distinct from the IgG memory repertoire and that this difference is likely the result of different stimuli. 9,11 Finally, the three Circos plots reveal the increased oligoclonality of both memory subsets compared with naïve. The colored ribbons in each plot represent V H -J H pairings that comprise at least 1% of the total subset repertoire.…”
Section: Resultsmentioning
confidence: 97%
“…The primers were selected for their ability to produce accurate, reproducible amplification of both naïve and mutated antibody repertoires, 12,13 and the variable gene use of our repertoire closely matched repertoire analysis in which amplification was performed on single B cells. 9 prominence of each V(D)J recombination within the repertoire of each cell subset (Figures 1a-c). These plots revealed a large number of trends that were apparent only when analyzing the repertoire in the context of complete V(D)J recombinations.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations